2022
DOI: 10.3390/su14095455
|View full text |Cite
|
Sign up to set email alerts
|

Using Digital Technologies for Testing Online Teaching Skills and Competencies during the COVID-19 Pandemic

Abstract: This study examines the online teaching abilities and competencies needed to teach online courses in Saudi Arabia’s higher education system. As a result, the goal of this study was to examine and expand the technology acceptance model (TAM) to assess online teaching abilities and competences utilizing digital technologies in higher education during the COVID-19 epidemic. Therefore, it aimed to develop a new model to measure and explore critical factors that influence online teaching skills, competencies, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…When users believe that the utilization of a specific information system could bolster their professional or academic performance [46], they would develop a positive attitude towards using that technology [31]. This relationship was also verified in the context of digital technologies in tertiary education [55]. For instance, the attitude towards the application of ICT-integrated mathematics instruction was positively impacted by the perceived usefulness [58].…”
Section: Research Hypothesismentioning
confidence: 80%
See 1 more Smart Citation
“…When users believe that the utilization of a specific information system could bolster their professional or academic performance [46], they would develop a positive attitude towards using that technology [31]. This relationship was also verified in the context of digital technologies in tertiary education [55]. For instance, the attitude towards the application of ICT-integrated mathematics instruction was positively impacted by the perceived usefulness [58].…”
Section: Research Hypothesismentioning
confidence: 80%
“…Similarly, a study on Chinese college students found a positive relationship between perceived ease of use and attitudes towards online learning [ 54 ]. Further evidence found that perceived ease of use of digital tools positively impacted attitudes towards their use in higher education [ 55 ]. Nevertheless, it is noteworthy that some studies have found no significant effect of perceived ease of use on attitudes [ 56 , 57 ].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Persons' knowledge background and living experience on computers or online systems. [26,39,40,41,42,43,44,45,46]…”
Section: Students' Background and Experiencementioning
confidence: 99%
“…The Technology Acceptance Model is used not only to understand the acceptance of various technologies, but it is also being applied to study critical skills in an educational setting. Such skills may include online teaching [2] , creativity [3] , and study skills [4] , and the model seems to be well-suited for comprehending computational thinking skills as well. The analytical approach employs a covariance-based structural equation model, encompassing three key phases: Confirmatory Factor Analysis, the construction of a measurement model, and the synthesis of a structural model.…”
Section: Introductionmentioning
confidence: 99%